PLANNING EVALUATION OF RIGID PAVEMENT’S THICKNESS ON INTERSECTION OF A ROAD SEGMENT OF SIKUI KM. 34 NATIONAL ROAD STA. 0+000 S/D 0+300 EAST BARITO DISTRICT - Agung Rubian Dwi Putra; Yasruddin Yasruddin (Universitas Lambung Mangkurat, 2021)
East Barito is one district that has a variety of natural resources such as agriculture and mining, Sikui KM of National Highway 34 is one of the roads that used to be accessed by one party mobilization of existing mines in Central Kalimantan. But on the other hand, the national road Sikui KM 34 is also used for connecting roads between provinces or cities. Based on the above actual national roads not intended for large-laden vehicles.Path planning is aimed to obtain a rigid pavement thickness based on the Pavement Design Manual Nomor 02/M/BM/2017 which controlled by “Pedoman Perencanaan Perkerasan Jalan Beton Semen Pd T-14-2003” and calculating the budget plan on the intersection of a road segment of Sikui KM 34 national road, East Barito disctrict.On the planning of rigid pavement’s thickness by using “Manual Desain Perkerasan Jalan Nomor 02/M/BM/2017” it is found that the concrete plate layer = 28,5 cm; LMC base layer = 10 cm; drainage layer = 15 cm and by using “Pedoman Perencanaan Perkerasan Jalan Beton Semen Pd T-14-2003” also found that the concrete plate layer = 21 cm; base layer = 15 cm. After that, on the existing condition obtained concrete plate layer = 30 cm; K-125 concrete layer = 10 cm. Then, it is found that the efficient pavement’s thickness which taken by using “Pedoman Perencanaan Perkerasan Jalan Beton Semen Pd T-14-2003” is more efficient rather than the existing condition. Moreover, this thesis also discusses the budget plan on the intersection of a road segment of Sikui Km. 34, East Barito district.